I am one You are one - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
S/he is one One in a million Welcome to a remarkable story. It is a story about the readers of a magazine, about who they are, what they do, and what they want of their magazine. A story about people who work in, and for, agriculture and rural...